2014
DOI: 10.1002/ajmg.a.36689
|View full text |Cite
|
Sign up to set email alerts
|

Nine children over the age of one year with full trisomy 13: A case series describing medical conditions

Abstract: Trisomy 13 (Patau syndrome), identified by Patau and colleagues [1960; Lancet 1: 790-793] is the third most common autosomal condition. Population studies indicate less than one in 10 children reaches their first birthday. In the face of mixed findings and recommendations for treatment, additional research is needed to further determine what contributes to longevity and implications for treatment for presenting medical conditions. The purpose of the present study is to report on presenting medical conditions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
0
12
0
3
Order By: Relevance
“…Although early mortality is still high, the children that do undergo surgical procedures have a good survival rate [4]. Palliative procedures, including gastrostomy tube placement [5], repair of atrial/ventricular septal defects and creation of oesophageal sphincters [6] are performed to improve quality of life. Therefore an in-depth discussion regarding the risks and benefits of the procedure, as well as the goals of care and the patient's overall prognosis, must take place with the child's parents and other physicians involved in the patient's care.…”
Section: Discussionmentioning
confidence: 99%
“…Although early mortality is still high, the children that do undergo surgical procedures have a good survival rate [4]. Palliative procedures, including gastrostomy tube placement [5], repair of atrial/ventricular septal defects and creation of oesophageal sphincters [6] are performed to improve quality of life. Therefore an in-depth discussion regarding the risks and benefits of the procedure, as well as the goals of care and the patient's overall prognosis, must take place with the child's parents and other physicians involved in the patient's care.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that the absence of holoprosencephaly may be an additional factor affecting the long‐term survival (Bruns & Campbell, ). To our knowledge, however, there are no reports mentioning other kinds of structural anomalies except holoprosencephaly.…”
Section: Disucussionmentioning
confidence: 99%
“…Despite the conventional understanding of trisomy 13 as lethal, a substantial number of children now survive longer than 1 year and undergo medical and surgical procedures as a part of their treatment, even as neonates (Bruns & Campbell, ; Nelson, Hexem, & Feudtner, ; Tsukada, Imataka, Suzumura, & Arisaka, ), and some children benefit from some interventions (Lantos, ; Nelson, Rosella, Mahant, & Guttmann, ). Indeed, the 5‐year survival rate of T13 was reported to be 9.7% (Meyer et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Baty et al [] notes that these children usually have on average of 2.2 surgical interventions in their first year of life. Bruns and Campbell [] describes the varying types of surgical interventions and Janvier et al [] noted increased survival to 1 year in children who receive such interventions [Janvier et al, ; Bruns and Campbell, ].…”
Section: Introductionmentioning
confidence: 99%